2009
DOI: 10.2214/ajr.07.4047
|View full text |Cite
|
Sign up to set email alerts
|

B-Mode Ultrasound With Algorithm Based on Statistical Analysis of Signals: Evaluation of Liver Fibrosis in Patients With Chronic Hepatitis C

Abstract: The grades of liver fibrosis in patients with chronic hepatitis C are well discriminated with the B-mode ultrasound-based analysis algorithm without discrimination between grades F0 and F1. Findings on conventional ultrasound images may reflect progression of liver fibrosis even in the absence of cirrhosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
71
0
6

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(80 citation statements)
references
References 20 publications
2
71
0
6
Order By: Relevance
“…The method is based on statistical analysis of the difference between theoretical and real echo amplitude distribution (21,22). Theoretical echo amplitude distribution indicates that a speckle pattern in a certain liver region is approximated by a function of a Reyleigh distribution based on the assumption that the speckle pattern is generated only by ultrasonic interference of very small scattering objects that are located closer than the wavelength of US.…”
Section: Study Populationmentioning
confidence: 99%
“…The method is based on statistical analysis of the difference between theoretical and real echo amplitude distribution (21,22). Theoretical echo amplitude distribution indicates that a speckle pattern in a certain liver region is approximated by a function of a Reyleigh distribution based on the assumption that the speckle pattern is generated only by ultrasonic interference of very small scattering objects that are located closer than the wavelength of US.…”
Section: Study Populationmentioning
confidence: 99%
“…18,19) On the other hand, the PDF of echo envelope amplitude from an inhomogeneous tissue such as a fibrotic liver deviates from the RA distribution; therefore, the deviation of the PDF from the RA distribution was quantified. [20][21][22] As a probability distribution model of a fibrotic liver, we proposed a multi-Rayleigh (MRA) model, which is a combination of several RA distributions with different variances. [23][24][25] Using the MRA model, liver fibrosis parameters such as the amount of fibrotic tissue and the fibrosis progressive ratio can be quantitatively estimated.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the attenuation [11,12] and backscatter coefficient [12] can be used to quantify the degree of fatty liver. Previous studies have shown that changes in the microstructures of liver parenchyma alter the speckle pattern and image texture of a B-mode image [13,14]. Therefore, the texture analysis of the B-mode image has also been explored for fatty liver evaluations [15][16][17].…”
Section: Introductionmentioning
confidence: 99%